2016
DOI: 10.1021/acs.organomet.6b00393
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Carbonylation of Oxorhenium Hydrides Induced by Lewis Acids

Abstract: Several oxorhenium hydride complexes with chelating diamidopyridine (DAP), diamidoamine (DAAm), and 2-mercaptoethyl sulfide (SSS) groups have been isolated and characterized. Adduct formation is observed when the DAP complex 1a is treated with the Lewis acid B­(C6F5)3. However, treatment of 1a,b with B­(C6F5)3 or BF3·OEt2 in the presence of CO results in reduction of the metal center by four electrons from Re­(V) to Re­(I).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…In previous work from our group we have shown that the oxorhenium hydride (O)­ReDAP­(H) ( 6a ) is reduced with CO to produce the Re (I) tricarbonyl 7 (Scheme ). The proposed mechanism for this reaction involves insertion of CO into the Re–H bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work from our group we have shown that the oxorhenium hydride (O)­ReDAP­(H) ( 6a ) is reduced with CO to produce the Re (I) tricarbonyl 7 (Scheme ). The proposed mechanism for this reaction involves insertion of CO into the Re–H bond.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Fischer carbene complexes with metals in high or intermediate oxidation states are quite rare, possibly because of the inability of metals to stabilize π-accepting carbonyl ligands. Our group has recently described a unique mechanism for the generation of rhenium­(V) acyl complexes that does not involve the prior formation of a carbonyl species but instead involves the direct insertion of CO into a Re–R (R = H, alkyl, aryl) bond. In this paper we show that this strategy can be utilized to generate rare Re­(III) and Re­(V) Fischer carbene complexes.…”
Section: Introductionmentioning
confidence: 89%
“…[52] Scheme5.Reactivity of rhenium oxidoa cetyl complexes towards boron Lewis acids. [25,53] creasingt he rate of olefin insertion (rate constant increased by af actor of 10 7 to 10 11 ).…”
Section: Influence Of Lewis Acid Coordination On Electronic Situationmentioning
confidence: 99%
“…Careful choice of the metal systemi sh owever crucial,a su ndesired furtherr eactivities may occur,s uch as complete scission of the metal oxido moiety or cleavage of the BÀCb ond in B(C 6 F 5 ) 3 .F or example, complete removal of the oxido group upon addition of the Lewis acid was observed in an oxidorhenium(V) hydride complex, where reactionw ith B(C 6 F 5 ) 3 under CO atmosphere led to ar eduction resulting in ac ationic triscarbonyl rhenium(I) complex. [53] Also, in ac erium(IV) aqua oxido compound, completes cission of aM =Ob ond occurred upon addition of B(C 6 F 5 ) 3 forming the dicationic cerium(IV) compound 33 with hydroxyborate anions(Scheme 9). [60,61] Carbon boron bond cleavage was observed in the reaction of vanadium oxido dimers of the type [{VO(L) 3 18) , [59] Lewis adduct 30,Mo =Ob ond length1 .8221(9) , [57] and ion pair 32 Ph , [57] MoÀOb ondlength 1.8975 (19) .…”
Section: Influence Of Lewis Acid Coordination On Electronic Situationmentioning
confidence: 99%
“…The same group in earlier work found that thermolysis of (DIP)Co(N 3 ) led to imine reduction via C–H activation . The reverse reaction, loss of hydrogen with formation of an imine donor functionality, has also been observed , . In addition, there are numerous examples of “reduction” of an imine arm through alkyl (instead of hydride) attack at the imine carbon , .…”
Section: Resultsmentioning
confidence: 98%